Three Cooperative Extension initiatives funded to address Michigan's opioid crisis - Eschbach, Cheryl L.; Contreras, Dawn A.; Kennedy, Lauren E. (Frontiers in Public Health, 2022)
People living with opioid use disorder and those experiencing other types of substance misuse are part of a public health crisis in the United States. Rates of opioid misuse, overdose, and opioid-related deaths within different subpopulations show where prevention efforts must focus. Through concerted efforts, aligned with common goals, a statewide community-based educational organization (Michigan State University Extension) has demonstrated ability to acquire multi-year funding from varied sources of state and federal funds that has produced robust support for statewide projects and collaborations. Researchers, educators, public health program managers, and other practitioners can benefit from learning how three funded initiatives in one state resulted in improved awareness and access for individuals and healthcare organizations. By sharing our implementation of health educational programs and presentations, other states' can adopt these evidence-based strategies for similar outreach. Cooperative Extension in Michigan delivers program series and one-time education to the public on the self-management of chronic conditions and pain, mindfulness for stress reduction, anger management, and opioid misuse prevention, treatment, and recovery. These evidence- and research-based health programs implemented by Extension staff teach participants common aspects of prevention such as self-management care, communication skills, self-efficacy, and goal setting or personal health action plans. Education aims to reduce dependency on opioids, prevent opioid misuse and share non-pharmacological solutions to pain management for those living with chronic conditions or at risk for developing dependence. The funded initiatives targeted rural residents, older adults, health care providers, and people living with chronic pain who may have access to prescription opioids. In addition to direct education, projects supported local communities with the development of coalitions, including the training of community partners to become program facilitators thereby increasing community capacity for prevention programs, and through the creation of patient referrals from healthcare settings to community-based education. In rural areas, Cooperative Extension plays a crucial role in connecting community resources to address healthy aging, and chronic disease or chronic pain self-management education. Community partners engaged in public health education and promotion, and healthcare providers alike may not be aware that Cooperative Extension plays a vital role in providing community-based health education.